Diagnostic Accuracy of Diffusion-Weighted Imaging in Multiparametric MRI in Detecting Carcinoma Prostate Taking Histopathology as Gold Standard - Khan, Taj Muhammad; Orakzai, Zubair Janan; Najm Ud Din; Humayoun; Abdul Wajid; Noureen, Sumaira (Indus Journal of Bioscience Research, 2025)
Background: Carcinoma prostate is a type of malignancy that is prevalent in geriatric males and is a leading cause of morbidity across the globe. Timely and proper diagnosis is the key to successful management. Multiparametric magnetic resonance imaging (mpMRI), especially diffusion-weighted imaging (DWI) has become an effective non-invasive diagnostic modality use to identify clinically relevant prostate cancer. Objective: To determine the diagnostic accuracy of diffusion-weighted imaging as part of multiparametric MRI in detecting carcinoma prostate, taking histopathology as the gold standard. Methods: This prospective study of diagnostic accuracy is a diagnostic accuracy study that was carried out at the Radiology Department, Mardan Medical Complex (MMC), MTI Mardan, during the period of November 2024 to May 2025. They included 150 male patients who were clinically suspected to have carcinoma prostate, but found in consecutive non-probability sampling. Every patient had a multiparametric MRI with diffusion-weighted imaging and apparent diffusion coefficient (ADC) mapping. PI-RADS version 2 was used to classify lesions, with a score of 3 or higher being positive. A gold standard was the histopathological examination. Data were broken with the help of SPSS version 25 and the parameters of diagnostic accuracy were calculated. Results: The mean age of patients was 65.2 ± 9.1 years, with the majority above 60 years. Histopathology confirmed carcinoma in 58.7% of patients. mpMRI demonstrated a sensitivity of 90.9%, specificity of 74.2%, positive predictive value of 83.3%, and negative predictive value of 85.2%, with an overall diagnostic accuracy of 84.0%. Lower ADC values were significantly associated with malignancy, and a strong negative correlation was observed between ADC values and Gleason score (r = -0.64, p < 0.001). Conclusion: Multiparametric MRI with diffusion-weighted imaging shows high sensitivity and good diagnostic accuracy in detecting carcinoma prostate. It serves as a reliable non-invasive tool for diagnosis, particularly for ruling out disease and guiding biopsy decisions